Perinatal and early infantile symptoms in congenital disorders of glycosylation1. Issue 3 (7th February 2013) - Funke, Simone; Gardeitchik, Thatjana; Kouwenberg, Dorus; Mohamed, Miski; Wortmann, Saskia B.; Korsch, Eckhard; Adamowicz, Maciej; Al‐Gazali, Lihadh; Wevers, Ron A.; Horvath, Adrienne; Lefeber, Dirk J.; Morava, Éva
Abstract Congenital disorders of glycosylation (CDG) are a rapidly growing family of inborn errors. Screening for CDG in suspected cases is usually performed in the first year of life by serum transferrin isoelectric focusing or mass spectrometry. Based on the transferrin analysis patients can be biochemically diagnosed with a type 1 or type 2 transferrin pattern, and labeled as CDG‐I, or CDG‐II. The diagnosis of CDG is frequently delayed due to the highly variable phenotype, some cases showing single organ involvement and others mimicking syndromes, like skeletal dysplasia, cutis laxa syndrome, or congenital muscle dystrophy. The aim of our study was to evaluate perinatal abnormalities and early discriminative symptoms in 58 patients consecutively diagnosed with diverse CDG‐subtypes. Neonatal findings and clinical features in the first months of life were studied in 36 children with CDG‐I and 22 with CDG‐II. Maternal complications were found in five, small for gestational age in nine patients. Five children had abnormal neonatal screening results for hypothyroidism. Congenital microcephaly and neonatal seizures were common in CDG‐II. Inverted nipples were uncommon with 5 out of 58 children. Dysmorphic features were mostly nonspecific, except for cutis laxa. Early complications included feeding problems, cardiomyopathy, thrombosis, and bleeding. Cases presenting in the neonatal period had the highest mortality rate. Survival in CDG patients is highly dependent on early intervention therapy. We recommend low threshold screening for glycosylation disorders in infants with neurologic symptoms, even in the absence of abnormal fat distribution. Growth retardation and neonatal bleeding increase suspicion for CDG. © 2013 Wiley Periodicals, Inc.